Islam and Knowledge: Harmony between Sciences and Faith - Fakhrurrazi, Fakhrurrazi; Wasilah, Nur; Jaya, Hendra (PT. Riset Press International, 2024)
This research examines the integration between Islam and science in the context of contemporary Islamic education. The primary focus of this research is to comprehend the harmony that can be achieved between scholarly pursuits and Islamic beliefs. The research method involves literature analysis and case studies on Islamic educational approaches that combine scientific principles with religious values. This study highlights the crucial role of Islamic education in providing a solid scholarly foundation while preserving moral and spiritual values. The discussion encompasses the integration of Islamic concepts into the curriculum, the implementation of teaching methods that combine critical thinking with Islamic ethical values, and how this approach can stimulate innovative thinking without compromising religious principles.The research findings indicate that an approach that creates harmony between Islam and science can strengthen the Islamic identity of learners while equipping them with knowledge relevant to the modern era. The practical implications of this research include guidelines for the development of Islamic education curricula that align religious values with the demands of the modern world, thus shaping a generation that is not only intellectually smart but also possesses a strong moral character.